Prevalence, risk factors and epidemiology of tobacco use among students; and the implementation of tobacco control polices in The Gambia - Jallow, Isatou K. (2019)
Background Tobacco consumption, and consequent morbidity and mortality, are expected to grow most markedly over the coming decades in Low and Middle Income Countries (LMICs). The WHO Framework Convention on Tobacco Control (FCTC) was developed in response to the globalisation of the tobacco epidemic and it presents a unique opportunity to reduce the global burden of tobacco. However, data on smoking in LMICs, particularly in sub-Saharan Africa as well as data on the progress of FCTC implementation are limited. The objectives of this thesis were to obtain a reliable and nationally representative estimate of prevalence of smoking, exposure to Second-Hand Smoke (SHS), smoking susceptibility and to identify the major risk factors among young people and to assess current implementation of tobacco control polices in The Gambia.